2019
DOI: 10.4025/actascitechnol.v41i2.37228
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of the roughness as function of cutting speed and feed rate (the roughness as function of machining parameters)

Abstract: Experimental evaluations based on statistical and scientific criteria play fundamental role in identification of optimal performance parameters in manufacturing engineering. Based on this premise, the Doehlert's experimental planning method was applied to external cylindrical turning process of ABNT 1045 steel, with the purpose of determining the roughness correlation as a function of the cutting speed (Vc) and feed rate (f). The Doehlert's matrix was defined with five levels for feed rate and three levels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Based on the connection function, Pei et al [8] analyzed the correlation of force signal, vibration signal and roughness signal in milling process, and got a better result. Rodrigues et al [9] applied correlation analysis to explore the degree of correlation between roughness and cutting speed and feed rate when turning 45-gauge steel in order to find the optimal configuration of the parameters. Thasthakeer et al [10] investigated the correlation between the variation of different parameters and the rate of change of cutting forces and surface roughness after machining.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the connection function, Pei et al [8] analyzed the correlation of force signal, vibration signal and roughness signal in milling process, and got a better result. Rodrigues et al [9] applied correlation analysis to explore the degree of correlation between roughness and cutting speed and feed rate when turning 45-gauge steel in order to find the optimal configuration of the parameters. Thasthakeer et al [10] investigated the correlation between the variation of different parameters and the rate of change of cutting forces and surface roughness after machining.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the connection function, Pei Hongjie [8] and others analyzed the correlation of force signal, vibration signal and roughness signal in milling process, and got a better result. Jean Robert Pereira Rodrigues [9] et al applied correlation analysis to explore the degree of correlation between roughness and cutting speed and feed rate when turning 45-gauge steel in order to find the optimal configuration of the parameters. Ahmad [10] et al investigated the correlation between the variation of different parameters and the rate of change of cutting forces and surface roughness after machining and found that this correlation was higher under wet machining conditions.…”
Section: Introductionmentioning
confidence: 99%